Atrocities on trial : historical perspectives on the politics of prosecuting war crimes - Heberer, Patricia Hrsg; Matthäus, Jürgen 1959- (Univ. of Nebraska Press, 2008)
The lessons of Leipzig : punishing German War criminals after the First World War / Jürgen Matthäus -- Early postwar justice in the American zone : the "Hadamar murder factory" trial / Patricia Heberer -- U.S. Army war crimes trials in Germany, 1945-1947 / Lisa Yavnai -- Law and politics in the subsequent Nuremberg trials, 1946-1949 / Jonathan Friedman -- The Nuremberg doctors' trial and the limitations of context / Michael R. Marrus -- "The scars of Ravensbrück" : medical experiments and British war crimes policy, 1945-1950 / Ulf Schmidt -- The Sachsenhausen trials : war crimes prosecution in the Soviet occupation zone and in West and East Germany / Jonathan Friedman -- "No ordinary criminal" : Georg Heuser, other mass murderers, and West German justice / Jürgen Matthäus -- Tainted law : the West German judiciary and the prosecution of Nazi War criminals / Rebecca Wittmann -- Justice in Austrian courts? The case of Josef W. and Austria's difficult relationship with its past / Patricia Heberer -- Crimes-against-humanity trials in France and their historical and legal contexts : a retrospective look / Richard J. Golsan -- Milestones and mythologies : the impact of Nuremberg / Donald Bloxham -- Prosecution, condemnation, and punishment : ethical implications of atrocities on trial / John K. Roth